Effect of Bosu Pilates on Primary Dysmenorrhea in Adolescent Girls - Mayuri T. Gotpagar1 , Poovishnu Devi2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Dysmenorrhea is a painful menstruation or a cramp labor like pain in the lower abdomen that radiates to upper abdomen, waist and thighs and sometimes accompanied by systemic symptoms like nausea, vomiting, diarrhea and dizziness. Dysmenorrhea can be treated by various pharmacological and non-pharmacological remedies. Incidence rate of dysmenorrhea among Indian girls is found to be 79.67%. It complicates the lives among adolescents females and affect the quality of life of many women. Pilates exercises is safe, non invasive treatment modality to relief pain of primary dysmenorrhea. Objectives: To study the effect of Bosu Pilates on primary dysmenorrhea in adolescent girls. Method: Ethical clearance was obtained from the institute committee. 25 women were screen from KARAD aged between 18 to 30 years. They were selected according to the inclusion and exclusion criteria. They were allowed to fill the form given which included the scale which rated the working, location, intensity, days of pain in dysmenorrhea. According to which conclusion was made. Result: After analyzing the data there was significant effect of exercises like stretching and core strengthening exercises performed on bosu ball which helped to reduce pain status in primary dysmenorrheal adolescent girls seen on Wong Baker scale (p=<0.0001). Conclusion: The study concludes that there was significant effect of bosu pilates on primary dysmenorrhea in adolescent girls.